Regulating the Black Box: A Comparative Policy Analysis of National Strategies for Governing Artificial Intelligence and Upholding Human Rights - Kouadio Koffi; Olivier Sossou; Aminatou Agounke (Yayasan Adra Karima Hubbi, 2026)
Background. The rapid development of artificial intelligence (AI) has raised significant concerns regarding its potential impacts on human rights, ethics, and governance. While AI promises advancements in efficiency and innovation, its opaque decision-making processes, often referred to as the